2016
DOI: 10.1104/pp.16.01150
|View full text |Cite
|
Sign up to set email alerts
|

Phytoglobins Improve Hypoxic Root Growth by Alleviating Apical Meristem Cell Death

Abstract: Hypoxic root growth in maize (Zea mays) is influenced by the expression of phytoglobins (ZmPgbs). Relative to the wild type, suppression of ZmPgb1.1 or ZmPgb1.2 inhibits the growth of roots exposed to 4% oxygen, causing structural abnormalities in the root apical meristems. These effects were accompanied by increasing levels of reactive oxygen species (ROS), possibly through the transcriptional induction of four Respiratory Burst Oxidase Homologs. TUNEL-positive nuclei in meristematic cells indicated the invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 51 publications
2
50
0
Order By: Relevance
“…This study shows that PGB1 is a key intermediate, linking ethylene signalling, via regulated NO removal, to O 2 sensing and hypoxia tolerance. This mechanism also provides a molecular explanation for the protective role of PGB1 during hypoxia and submergence described in prior studies 31,3638 . Natural variation for ethylene-induced hypoxia adaptation was also observed in wild species and correlated with PGB1 induction 10 .…”
Section: Discussionsupporting
confidence: 61%
“…This study shows that PGB1 is a key intermediate, linking ethylene signalling, via regulated NO removal, to O 2 sensing and hypoxia tolerance. This mechanism also provides a molecular explanation for the protective role of PGB1 during hypoxia and submergence described in prior studies 31,3638 . Natural variation for ethylene-induced hypoxia adaptation was also observed in wild species and correlated with PGB1 induction 10 .…”
Section: Discussionsupporting
confidence: 61%
“…Reports regarding the influence of nitric oxide on a plant's ability to cope with hypoxia are controversial (Perazzolli et al, 2004;Gupta and Igamberdiev, 2016;Mira et al, 2016;Peng et al, 2016), making it hard to draw conclusions regarding the impact of the described regulation under hypoxia. However, ERF-VII behavior as novel NO sensors has made it possible to connect them to the physiology of this gaseous signal.…”
Section: Erf-vii Involvement In Ros-and No-dependent Responsesmentioning
confidence: 99%
“…In maize roots under hypoxic (oxygen-deficient) conditions, expression of genes encoding the A, B, C, and D isoforms of Zm-RBOH is stimulated during the cell death of the apical meristem (Mira et al, 2016). Previously, we found that waterlogging induces Zm-RBOHH expression in the cortical cells of primary roots at the same time it induces aerenchyma formation .…”
Section: Introductionmentioning
confidence: 98%